2014
DOI: 10.1371/journal.pone.0092824
|View full text |Cite
|
Sign up to set email alerts
|

CypA, a Gene Downstream of HIF-1α, Promotes the Development of PDAC

Abstract: Hypoxia-inducible factor-1α (HIF-1α) is a highly important transcription factor involved in cell metabolism. HIF-1α promotes glycolysis and inhibits of mitochondrial respiration in pancreatic ductal adenocarcinoma (PDAC). In response to tumor hypoxia, cyclophilin A (CypA) is over-expressed in various cancer types, and is associated with cell apoptosis, tumor invasion, metastasis, and chemoresistance in PDAC. In this study, we showed that both HIF-1α and CypA expression were significantly associated with lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 39 publications
(57 reference statements)
4
34
1
Order By: Relevance
“…Therefore, the study of hypoxic microenvironments may have a crucial function in targeted therapy adopted by clinics in the future. Hypoxia-inducible factor-1α (HIF-1α) is an essential transcriptional regulatory factor in hypoxia microenvironments and has 100 types of downstream gene, including cell proliferation, angiogenesis and energy metabolism (8,9). A previous study indicated that the expression of HIF-1α, C-X-C motif chemokine receptor 4 (CXCR4) and vascular endothelial growth factor (VEGF) is involved in tumor progression, angiogenesis, metastasis and survival, and their expression may be induced by hypoxia (10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study of hypoxic microenvironments may have a crucial function in targeted therapy adopted by clinics in the future. Hypoxia-inducible factor-1α (HIF-1α) is an essential transcriptional regulatory factor in hypoxia microenvironments and has 100 types of downstream gene, including cell proliferation, angiogenesis and energy metabolism (8,9). A previous study indicated that the expression of HIF-1α, C-X-C motif chemokine receptor 4 (CXCR4) and vascular endothelial growth factor (VEGF) is involved in tumor progression, angiogenesis, metastasis and survival, and their expression may be induced by hypoxia (10).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophilin A (CyPA) was originally discovered as a cellular factor with high affinity for the immunosuppressant cyclosporine A (CsA) [6]. Previous studies have demonstrated that ischemia/reperfusion (I/R) and hypoxia can induce expression of CyPA [7][8][9]. CyPA can be also secreted from monocytes/macrophages [10], endothelial cells [11], and vascular smooth muscle cells [12] in response to ROS.…”
mentioning
confidence: 99%
“…Consistent with that, loss of CypA expression increased mitochondrial membrane depolarization and reduced survival following H 2 O 2 treatment [34]. Furthermore, there is evidence that CypA is transcriptionally regulated by the hypoxia inducible factor (HIF)-1α under hypoxic conditions [34] [61] and it is suggested that up-regulated CypA desensitises cells to hypoxia-induced cell death [34].…”
Section: Cyclophilins and Chemoresistancementioning
confidence: 59%